A Contribution to the Study of the Forming of Dry Unidirectional HiTape® Reinforcements for Primary Aircraft Structures - Bouquerel, Laure; Moulin, Nicolas; Drapier, Sylvain (Frontiers in Materials, 2021)
In the context of developing competitive liquid composites molding processes for primary aircraft structures, modeling the forming stage of automatically-placed initially flat stacks of dry reinforcements is of great interest. In the case of HiTape(R), a dry unidirectional carbon fiber reinforcement designed to achieve performances comparable to state-of-the-art pre-impregnated materials, the presence of a thermoplastic veil on each side of the material for both processing and mechanical purposes should also be considered when modeling forming in hot conditions. As a dry unidirectional reinforcement, HiTape(R) is expected to exhibit a transversely isotropic behavior. Computation cost and strong characterization challenges led us to model its behavior at the forming process temperature (above the thermoplastic veil melting temperature) through a homogeneous equivalent continuous medium exhibiting four ‘classical’ deformation modes and a specific structural mode, namely out-of-plane bending. The response of both single plies and stacks of HiTape(R) to this latter structural mode was characterized at the forming process temperature using a modified Peirce flexometer. Results on single plies showed a non-linear softening moment-curvature behavior and a corresponding flexural stiffness much lower than what can be inferred from continuum mechanics. Moreover, testing stacks revealed that the veil acts as a thin load transfer layer between the plies undergoing relative in-plane displacement, i.e. inter-ply sliding. This inter-ply response was then characterized separately at the forming process temperature thanks to a specific method relying on a pull-through test. Experiments performed at pressures and speeds representative of the forming stage revealed that a hydrodynamic lubricated friction regime predominates, i.e. a linearly increasing relationship between the friction coefficient and the modified Hersey number. From an industrial point of view, high forming pressures and low speeds are therefore recommended to promote inter-ply slip to limit the occurrence of defects such as wrinkles.